2019
DOI: 10.1016/j.foodchem.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real-time PCR methods for quantification of European hake (Merluccius merluccius) in processed food samples

Abstract: The quantification of species in commercial products is limited by analytical shortcomings, as most of them provide semiquantitative results. An exception is real-time PCR, which can provide quantitative results using hybridization probes. In the present work, this technique has been applied to the absolute, absolute-relative and relative quantification of the most valued hake species in European markets, Merluccius merluccius (European Hake). The best quantification results for this species in binary mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the literature, there is a large number of methods to quantify material of animal or plant origin in food products [13,41]. Some of these methods are not suited for processed food products, and were therefore not considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is a large number of methods to quantify material of animal or plant origin in food products [13,41]. Some of these methods are not suited for processed food products, and were therefore not considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez A. et al [40] describe the use of real-time PCR for absolute, absolute-relative and relative quantification of the most valued hake species in European markets, European hake (Merluccius merluccius). The authors compared two systems, nuclear and mitochondrial.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The research showed that the best quantification results for this species in binary mixtures with non-target species (Merluccius capensis) and using the species-specific realtime PCR system were achieved with a relative quantification approach. It was demonstrated that absolute quantification using the nuclear system was appropriate for the quantification of the Merluccius genus in food model samples [40].…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Floren et al, 2015;Thomas et al, 2016;Ushio et al, 2018). Quantifying input biomass from DNA analysed in fish products is an emerging area of research and has a large unexplored potential in comparison to traditional visual identification, especially in samples where the morphological characteristics are sparse or absent (Nagase et al, 2010;Bojolly et al, 2017;Sánchez et al, 2019). Further, DNA, particularly mitochondrial DNA (mtDNA), has been found suitable for species detection and quantification even when products are highly processed (e.g.…”
Section: Introductionmentioning
confidence: 99%